Physical and Chemical Properties of Native and Fully Pregelatinized Cassava Starch (Manihot esculenta Crantz) - Dewantara Putra, I Gusti Ngurah Agung; Murwanti, Retno; Rohman, Abdul; Sulaiman, T.N Saifullah (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
Starch is widely used as an excipient in pharmaceutical formulations because it is inert and it can be mixed with drugs without any chemical reactions. This study was aimed to develop and to characterize the physical and chemical properties of cassava starch fully pregelatinized (CSFP) and native cassava starch (Manihot esculenta Crantz) (NCS). Organoleptic properties, pH, ash content, shrink drying, macroscopic and microscopic analyses, amylose and amylopectin content, bulk and tapped density, the angle of repose and flow rate were physically evaluated for both type of cassava starch. Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), energy-dispersive x-ray spectroscopy (EDS), and differential scanning calorimetry (DSC) were used to characterize and evaluate the chemical properties of the CSFP and NCS. The results of this study indicate that CSFP exhibited different values of those determined parameters compared to that of NCS organoleptic properties i.e, pH, viscosity, ash content, shrink drying, macroscopic and microscopic analyses, amylose and amylopectin content, bulk and tapped density, angle of repose and flow rate. The measurement results with DSC obtained Tg at NCS of 68.18oC while in CSFP there is no Tg because cassava starch (CS) is fully gelatinized. In conclusion, CSFP as a good profile starch contained a higher amount of amylose with larger particle size and good particle density and viscosity than the natural starch and improve its flow properties and compactibility. CSFP had a noticeable effect on fragility, hardness, disintegration time and percentage of drug release from the tablets produced, that can be developed as a pharmaceutical excipient in development of solid dosage forms (sustain release).